Oral health status in relation to socioeconomic and behavioral factors among pregnant women: a community-based cross-sectional study - Marzie Deghatipour; Zahra Ghorbani; Shahla Ghanbari; Shahnam Arshi; Farnaz Ehdayivand; Mahshid Namdari; Mina Pakkhesal (BMC, 2019)
Abstract Background Oral health of women during pregnancy is an important issue. Not only it can compromise pregnancy outcomes, but also it may affect their newborn's overall health. The aim of this study was to assess the oral health status and associated factors in pregnant women. Methods A cross-sectional study was conducted amongst 407 pregnant women in the second and third trimester of pregnancy in Varamin, Iran. Oral health status was examined, and demographic, socioeconomic status and dental care behavior data were collected. Oral health indices included periodontal pocket, bleeding on probing (BOP) and decayed, missed, filled teeth (DMFT). Regression analysis of DMFT was used to study the association between demographic, dental care behaviors indicators and outcome variables using the count ratios (CR) and 95% confidence intervals (CI). Results The mean (SD, Standard Deviation) age of participants was 27.35 (5.57). Daily brushing, flossing habit were observed in 64.1, and 20.6% of mothers, respectively. Mean (SD) of DMFT, D, M, F were 10.34(5.10), 6.94(4.40), 2.22 (2.68) and 1.19(2.23), respectively. Women older than 35 years had significantly more DMFT [CR = 1.35 (95% CI 1.13; 1.60)], less D [CR = 0.75 (95% CI 0.59; 0.94)], and more M [CR = 3.63 (95% CI 2.57; 5.14)] compared to women under 25 years after controlling for education and dental care behaviors. Women with academic education had significantly less decayed teeth [CR = 0.63 (95% CI 0.48; 0.84)], compared to women with under 12 years of education. Conclusions Oral health status of pregnant women was not satisfactory, having an average of seven decayed teeth in their mouth.